“AMUKTI PALAPA” NATIONAL INSIGHTS FOR THE MILENNIAL GENERATION AS AN EFFORT TO IMPROVE NATIONAL UNITY - wikan sasmita; Agus Widodo; Etty Andyastuti; Nursalim Nursalim; Suratman Suratman; Yuanita Dwi Pristiani; Irawan Hadi Wiranata; Fitta Nurisma Riswandi; Hamidah Ulfa Fauziah (SOSIOEDUKASI, 2024)
Ideological issues have a huge impact. The unity and unityof the nation becomes a phenomenon related to the ideology of Pancasila, of course, the rules tha govern the life of the nation and state of Indonesia. When ideology is problematic of course the unity and unity of the nation becomes unshaven so that aspects of the life of the nation will be problematic. In the early stages, efforts to solve the problem is to diagnose the condition of millennial youth, whether they still hold firm to the values of unity and unity of the nation or not. So the resilience of Pancasila ideology in Indonesia especially sees abaout how the younger generation (Millennials) understand and implement Pancasila properly and correctly. The method of national insight in Tiron village of Banyakan districts of Kediri uses questionnaires to estimate how much insight the level of nationality. The results of the court (sosialization of national insight) from 25 participants of karang taruna show a high national insight. The conclusion shows that the license (sosialization of national insight) can improve national insight for millennial youth of Tiron Vilage, Banyakan district of Kediri regency